ANALISIS PRIORITAS PROGRAM PEMBERDAYAAN MASYARAKAT DALAM PEMULIHAN EKONOMI MASYARAKAT PASCA PANDEMI COVID-19 - Agus Lukman Hakim; Rahmat Maulana; Zaenal Abidin; Ali Salmande; M Robbi Qawi; Haryo Setyoko; Reni Tania (LP2M Universitas Bina Bangsa, 2022)
The Covid-19 pandemic condition requires all parties to be able to carry out their activities according to new habits. The Serang Regency Government is trying to carry out community economic recovery activities. Therefore, community empowerment activities are needed that need to be prioritized in the economic recovery of the community after the pandemic. The research approach used is descriptive quantitative. Research respondents are experts consisting of academics and practitioners who take part in and contribute to community empowerment programs. The analysis technique used is Urgency, Seriousness, Growth (USG) analysis. The results showed that first, there were 12 activities that had high ultrasound values. It is necessary to support priority activities and budgets for implementation. Second, there are 31 activities that have a moderate category. With this category, the activities can continue to be carried out because they are beneficial in the economic recovery of the community after the Covid-19 pandemic, even though the impact of the benefits is moderate. Third, there are 12 activities that are categorized as low so that the government needs to evaluate and improve these activities with activities that are more beneficial for the community's economic recovery